Dampak Perselingkuhan Terhadap Hubungan Rumah Tangga Suami Istri : (Analisis Perkara Melalui Mediasi di Pengadilan Agama Jambi) - Dewanti, Aziz; Umar, M. Hasbi; Hidayati, Rahmi (Muhammadiyah University of Surabaya, 2025)
This study aims to examine infidelity in the jurisdiction of Jambi province against marital relationships, the factors that cause infidelity and the legal consequences caused by infidelity with the main focus on case analysis through mediation at the Jambi Religious Court.This study will apply a qualitative method that includes data collection from observations, interviews, and data sources related to the phenomenon being studied. For the data analysis technique, pre-field analysis was used, field data analysis of the miles and huberman model and spradley data analysis. The results of the study show that the factors that cause infidelity in the jurisdiction of Jambi province are generally classified into two, namely internal factors and external factors. However, in general, infidelity cases at the Jambi Religious Court that cause continuous disputes and quarrels are one of the parties finding a phone call or chat with another dream man or woman as well as direct information obtained from relatives or friends by showing evidence of infidelity from the partner. Infidelity has a large and serious impact on domestic relationships. Based on the case at the Jambi religious court, the impact of infidelity is not only felt by both the victim and the perpetrator between married couples, but also to their children, then the family or closest relatives even have an impact on their life in the community. The legal consequences arising from infidelity are the breakdown of marriage or divorce, child custody and the division of property. Keywords: Infidelity, Mediation, Jambi Religious Court